ANALISIS EFEKTIVITAS DAN KONTRIBUSI PBB P2 TERHADAP PENDAPATAN ASLI DAERAH KABUPATEN PURWOREJO TAHUN 2015 – 2017 - , (Politeknik Sawunggalih Aji, 2022)
Land and Building Tax (PBB) is a central tax, but it becomes regional revenue because the proceeds of revenues are mostly left to the Regional Government. The purpose of this study was to determine the level of effectiveness of Rural and Urban Land and Building Taxes (PBB P2) of Purworejo Regency in 2015-2017 and find out the level of contribution of Land and Building Tax (PBB P2) to Purworejo District Original Revenue (PAD) in 2015-2017 . Data collection techniques are carried out by observation, interviews and documents. This research uses descriptive qualitative method, which is more emphasis on the description of the sentence or explanation and quantitative descriptive, namely the analysis of data in the form of numbers. This study concluded that the effectiveness of PBB P2 in Purworejo District for 16 sub-districts in 2015 and 2016 included quite effective criteria and effective criteria. Whereas in 2017 for 16 sub-districts including criteria are less effective (3 sub-districts), quite effective (8 sub-districts) and effective (5 sub-districts). The level of PBB P2 contribution to the Regional Original Revenue of Purworejo Regency decreases every year and below 10% including the very poor contribution criteria. 2015 was 8%, 2016 was 7% and 2017 was 6%.